2014
DOI: 10.1177/2329488414525444
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Visualization in the Communication of Business Strategies

Abstract: An experiment was conducted to gather empirical evidence regarding whether the use of visualization is better than text in the communication of a business strategy. A total of 76 managers saw a presentation of the strategy of the financial services branch of an international car manufacturer. The visual representation of the strategy was chosen as the independent variable, and the effects on the audience were measured. Three types of visual support were chosen as conditions: bulleted list, visual metaphor, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…From the need for storytelling to reach diverse audiences and sell ideas (Barker & Gower, 2010;Nishi, 2013), to the use of visual images to increase listeners' attention and recall of information (Kernbach, Eppler, & Bresciani, 2014), to the need to be concise in an age of shrinking attention spans (Evans, 2014), PechaKucha presentations can prepare students for those demands. Not only does research indicate that students' demonstrated communication competence is as strong or stronger in PechaKucha presentations as it is with traditional speaking styles (Beyer, 2011;Oliver & Kowalczyk, 2013), but students also view these presentations as "fun."…”
mentioning
confidence: 99%
“…From the need for storytelling to reach diverse audiences and sell ideas (Barker & Gower, 2010;Nishi, 2013), to the use of visual images to increase listeners' attention and recall of information (Kernbach, Eppler, & Bresciani, 2014), to the need to be concise in an age of shrinking attention spans (Evans, 2014), PechaKucha presentations can prepare students for those demands. Not only does research indicate that students' demonstrated communication competence is as strong or stronger in PechaKucha presentations as it is with traditional speaking styles (Beyer, 2011;Oliver & Kowalczyk, 2013), but students also view these presentations as "fun."…”
mentioning
confidence: 99%
“…The adage "a picture is worth a thousand words" exists for good reason, and emphasizes the suggestion that a successful communication strategy should be holistic and should have both verbal and visual elements. At the organizational level, it is known and widely accepted that visual representations outperform text (Kernbach et al, 2015). However, visual representations of corporate strategies imply a different communication strategy than pictures of individuals who belong to an organization.…”
Section: Practical Implications and Conclusionmentioning
confidence: 99%
“…In a careful study, Rogers, Gunesekera, and Yang (2011) analyzed two versions of a philosophy and strategy statement to find out which language a company used to avoid ambivalence after a deep crisis. Kernbach, Eppler, and Bresciani (2015) could recently show in an experimental study that boundary objects in form of visualizations of a strategy were significantly better than text in terms of the achieved attention, agreement, and retention. This implies that visual boundary objects whose ambiguity tends to be high may increase the motivation to jointly fathom the meaning of boundary object across organizational units.…”
Section: Conceptualizationmentioning
confidence: 99%